F(x)=x^2+2x+1 & g(x)=3(x+1)^2
now, f(x)+g(x)
=x^2+2x+1+3(x+1)^2
=x^2+2x+1+3(x^2+2x+1)
=x^2+2x+1+3x^2+6x+3
=4x^2+8x+4<===answer(c)
next:
f(x)=x^2-1 & g(x)=x+3
now, f(g(x))=(x+3)^ -1
=x^2+6x+9-1
=x^2+6x+8<====answer(b)
i solve two of ur problems.
now try the 3rd one that is similar to no. 1
and try the last two urself.
Answer:
5 out of 9
Step-by-step explanation:
Answer:
8 87/100 = 887/100
Step-by-step explanation:
"Eight and eighty-seven hundredths" is ...
8 87/100 = 887/100
Hi!
If they each got the same, then they each got 1/3 of the total $360. Therefore, we can divide 360 by 3. We can do this by dividing 36 by 3, 36/3, and that's 12. Then add the 0! 120.
Your sentence could be: "The amount of money each worker got can be represented by 360/3, which is $120."
Hope this helps! :D
D. y = 6x...subbing in (2,12)...x = 2 and y = 12
12 = 6(2)
12 = 12 (correct)
so (2,12) is a solution to : y = 6x